PERSPEKTIF KRIMINOLOGI KONTEMPORER TERHADAP KRIMINALITAS REMAJA DI ERA MEDIA SOSIAL - Sintia Aprilia Sari; Erna Dewi; Fristia Berdian Tamza (JOURNAL OF LAW AND NATION, 2026)
The development of social media has significantly changed the patterns of adolescent social interaction and has also influenced the dynamics of juvenile crime. This article aims to analyze the phenomenon of juvenile crime in the social media era through a contemporary criminological perspective. The approach used is normative research with conceptual analysis of modern criminological theories such as social learning theory, general strain theory, routine activity theory, and cybercriminology. The results of the study indicate that social media acts as a space for the reproduction of values, an arena for identity search, and a facilitative medium for crimes such as cyberbullying, online fraud, the distribution of illegal content, and violence triggered by digital exposure. Structural, psychological, and cultural factors interact in shaping adolescent deviant behavior. Therefore, countermeasures strategies cannot rely solely on repressive approaches but must emphasize digital literacy, strengthening informal social control, and prevention-based policies.